PROGNOSIS OF ONE-DAY MORTALITY AND PROTEIN GROWTH AND DAMAGE FACTORS IN ACUTE CORONARY SYNDROME - G. Kh. Kayumova; V. A. Razin; R. Kh. Gimaev; V. I. Ruzov; О. L. Arjamkina; V. V. Gnoevykh (Кардиоваскулярная терапия и профилактика)
Aim. To perform comparative analysis of the pregnancy-associated plasma protein A and insulin-like growth factor 1 (PAPP-A and IGF-1) in blood plasma of patients with acute coronary syndrome (ACS). Prediction of 24-hour risk of fatal outcome in ACS.Material and methods. The concentrations of PAPP-A and IGF-I were assessed in 71 ACS patients, mean age 57 y. o. In the study group, during 24 hours myocardial infarction (MI) was diagnosed in 44, unstable angina in 27, and 9 fatal outcomes. Also, the concentrations of PAPP-A and IGF-I were measured in comparison and control groups. Comparison consisted of 40 hypertension patients with stable ischemic heart disease. Controls were 20 almost healthy persons.Results. In the study, there was increase of PAPP-A and IGF-I levels in ACS patients. In unstable angina patients PAPP-A is higher than in controls 3,56 times, and in MI patients 11,6 times. In MI, PAPP-A is 3,2 times higher than in unstable angina. In unstable angina patients there the highest levels of IGF-I, and 1,27 higher than in controls. In the study, we showed that IGF-I and PAPP-A levels in acute coronary pathology are linked to the outcome at the first day of the disease.Conclusion. It is aim full to apply PAPP-A and IGF-I to urgent cardiology practice as an analyzer of atherosclerotic plaque instability in acute coronary events, as a factor of life and disease prognosis.